Productivity, investment in ICT and market experimentation: micro evidence from Germany und the US - John Haltiwanger; Ron Jarmin; Thorsten Schank (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2003)
This paper examines the relationship between the use of advanced technologies such as ICT, and outcomes such as productivity, the skill mix of the workforce and wages using micro data for the U.S. and Germany. We find support to the idea that U.S. businesses engage in experimentation in a variety of ways not matched by their German counterparts. In particular, there is greater experimentation amongst young U.S. businesses and also among those actively changing their technology. This is evidenced in a greater dispersion in productivity and related key business choices. We also find that the mean impact of adopting new technology on productivity and wages is greater the in U.S. than in Germany. – – Dieses Papier untersucht die Beziehung zwischen dem Einsatz neuer Technologien, wie von IKT, und betrieblichen Kenngrößen wie der Produktivität, der Qualifikationsstruktur und den Löhnen, wobei Mikrodaten für die USA und Deutschland verwendet wurden. Dabei kann die Hypothese unterstützt werden, dass in den USA Betriebe stärker experimentieren - gemessen anhand der Streuung der Produktivität und anderen betrieblichen Entscheidungsvariablen - als in Deutschland. Dies zeigt sich insbesondere bei jungen Betrieben und bei Betrieben, die ihre Technologie verändern. Wir finden ebenfalls einen größeren durchschnittlichen Einfluss der Einführung neuer Technologien auf die Produktivität und die Löhne in den USA als in Deutschland.
Keywords: D20; D24; O30; 330; ICT; Experimentation; Productivity; Internet Use; U.S.; Germany; Unternehmensgründung; Computergestütztes Verfahren; Informationstechnik; Technologiewahl; Produktivität; Internet; Lohn; Qualifikation; Deutschland; USA